Interleukin 1 receptor antagonist (IL1RN) gene variants predict radiographic severity of knee osteoarthritis and risk of incident disease. Issue 3 (18th December 2019) - Attur, Mukundan; Zhou, Hua; Samuels, Johathan; Krasnokutsky, Svetlana; Yau, Michelle; Scher, Jose U; Doherty, Michael; Wilson, Anthony G; Bencardino, Jenny; Hochberg, Marc; Jordan, Joanne M; Mitchell, Braxton; et al.
Abstract : Objective: In these studies, we examined the association of single nucleotide polymorphisms (SNPs) of the IL1RN gene with radiographic severity of symptomatic knee osteoarthritis (SKOA) and the risk of incident OA. We also explored these genetic polymorphisms in patients with new onset rheumatoid arthritis (RA). Methods: Over 1000 subjects who met American College of Rheumatology criteria for tibiofemoral OA were selected from three independent, National Institute of Health (NIH)-funded cohorts. CTA and TTG haplotypes formed from three SNPs of the IL1RN gene (rs419598, rs315952, rs9005) were assessed for association with radiographic severity, and risk for incident radiographic OA (rOA) in a nested case–control cohort. These IL1RN haplotypes were also assessed for association with disease activity (DAS28) and plasma inflammatory markers in patients with RA. Results: Carriage of the IL1RN TTG haplotype was associated with increased odds of more severe rOA compared with age-matched, sex-matched and body mass index-matched individuals. Examination of the osteoarthritis initiative Incidence Subcohort demonstrated that carriage of the TTG haplotype was associated with 4.1-fold (p=0.001) increased odds of incident rOA. Plasma IL-1Ra levels were lower in TTG carriers, while chondrocytes from TTG carriers exhibited decreased secretion of IL-1Ra. In patients with RA, the TTG haplotype was associated with increased DAS28, decreased plasma IL-1Ra and elevations of plasma inflammatory markers (hsCRP, interleukin 6 (IL-6)). Conclusion: Carriage of the IL1RN TTG haplotype is associated with more severe rOA, increased risk for incident OA, and increased evidence of inflammation in RA. These data suggest that the IL1RN TTG risk haplotype, associated with decreased IL-1Ra plasma levels, impairs endogenous 'anti-inflammatory' mechanisms.